Synopsis in the Management of Urinary Incontinence - Alhasso, Ammar; Bekarma, Holly (IntechOpen, 2017)
The prevalence of urinary incontinence increases with age. It has recognised social and psychological impact on individuals as well as a financial implication to individuals and healthcare systems. The book attempt to discuss the assessment of urinary incontinence, followed by surgical and conservative treatment options in a concise way, within the framework of clinical practice. We would like to acknowledge all the authors for their hard work in completing this book.